BACKEND DESIGN OF A WEBSITE-BASED INTERNAL QUALITY AUDIT SYSTEM WITH AMI FEATURES, DIGITAL SIGNATURES, AND DATA SEARCH USING PROTOTYPING - Hasman Budiadi; Ayuni Tiyasari; Setiyowati (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Internal quality audit is an important part of the Internal Quality Assurance System (SPMI) to ensure that activities in higher education run according to predetermined standards and improve quality on an ongoing basis. At Tiga Serangkai University, AMI activities are still carried out manually, so they tend to be less than optimal in terms of speed, efficiency, and accuracy of audit data management. This study aims to develop a website-based internal quality audit system, named SIAMI (Sistem Informasi Audit Mutu Internal), to facilitate audit management at LPM Tiga Serangkai University. The method used in developing this system is prototyping. This system was built using the Laravel framework and MySQL database by implementing the AMI feature flow, digital signature feature, and audit data search feature. The results of this study produced the SIAMI application that can assist LPM in managing audit data efficiently and structured, successfully transitioning the audit process from manual to digitalization.